In Situ Electrochemical Mn(III)/Mn(IV) Generation of Mn(II)O Electrocatalysts for High-Performance Oxygen Reduction - Tian, Han; Zeng, Liming; Huang, Yifan; Ma, Zhonghua; Meng, Ge; Peng, Lingxin; Chen, Chang; Cui, Xiangzhi; Shi, Jianlin (Nano-Micro Letters, 2020)
Among various earth-abundant and noble metal-free catalysts for oxygen reduction reaction (ORR), manganese-based oxides are promising candidates owing to the rich variety of manganese valence. Herein, an extremely facile method for the synthesis of cubic and orthorhombic phase coexisting Mn(II)O electrocatalyst as an efficient ORR catalyst was explored. The obtained MnO electrocatalyst with oxygen vacancies shows a significantly elevated ORR catalytic activity with a half-wave potential (E1/2) of as high as 0.895 V, in comparison with that of commercial Pt/C (E1/2 = 0.877 V). More impressively, the MnO electrocatalyst exhibits a marked activity enhancement after test under a constant applied potential for 1000 s thanks to the in situ generation and stable presence of high-valence manganese species (Mn3+ and Mn4+) during the electrochemical process, initiating a synergetic catalytic effect with oxygen vacancies, which is proved to largely accelerate the adsorption and reduction of O2 molecules favoring the ORR activity elevation. Such an excellent ORR catalytic performance of this MnO electrocatalyst is applied in Zn–air battery, which shows an extra-high peak power density of 63.2 mW cm−2 in comparison with that (47.4 mW cm−2) of commercial Pt/C under identical test conditions. Highlights: 1 MnO rich in oxygen vacancies has been synthesized. 2 The synthesized MnO demonstrates excellent oxygen reduction reaction performance and high output power in Zn–air battery. 3 The high catalytic activity is attributed to the synergetic catalytic effect between oxygen vacancies and in situ generated Mn3+/Mn4+.